This equation can be expressed in the form **(x+a)(y+b) = c ** for some constants **a,b,** and **c **Enter your answer in the form "a,b,c".

I get this is a rational function and it needs to be changed into a hyperbolic function but I got stuck on how to do that help would be greatly appreciated guys. Thanks for all your hard work on this forum!

thesoccerfish May 11, 2020

#1**+1 **

**This equation can be expressed in the form \((x+a)(y+b) = c\) for some constants a,b, and c**

\(\begin{array}{|rcll|} \hline \mathbf{y} &=& \mathbf{\dfrac{x-3}{x+7}} \\\\ y(x+7) &=& x-3 \\ yx+7y &=& x-3 \\ yx+7y-x &=& -3 \\ x(y-1)+7y &=& -3 \\ x(y-1)+7y-7+7 &=& -3 \\ x(y-1)+7(y-1)+7 &=& -3 \\ x(y-1)+7(y-1) &=& -10 \\ (y-1)(x+7)&=& -10 \\ \mathbf{(x+7)(y-1)} &=& \mathbf{-10} \\ \hline \end{array}\)

heureka May 11, 2020